Predicting the Impact of Customer Value as a Mediating Influence on Timeliness, Order Fulfillment, Information Quality, Customer Focus in Customer Loyalty - Arie Indarwanto; Rahmat Agus Santoso; Eva Desembrianita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The importance of sea transportation and logistics services in supporting the smooth running of foreign trade (exports), then shipping and logistics service facilities are one of the most important. Related to this, many shipping and logistics business sectors have sprung up. The shipping and logistics business sector includes an activity using ships or air to transport goods from one country to another. Objective – To analyze the Predicted Impact of Customer Value as a Mediating Influence on Timeliness, Order Fulfillment, Information Quality, Customer Focus in Customer Loyalty. Because customer loyalty is a concept of marketing objectives that provide the continuity of the company to obtain the profits. Design / methodology / approach – Based on the objectives to be achieved, this research is an explorative research because the aim is to find and predict the Impact of Customer Value as a Mediating Effect on Timeliness, Order Fulfillment, Information Quality, Customer Focus in Customer Loyalty. This research is the development of problem solving (Malhotra, 2012) which aims to determine the impact prediction on customer loyalty. Findings – The results of this study indicate that the Prediction of Customer Value Impact as Mediating Influence has an indirect influence on Timeliness, Order Fulfillment, Information Quality, and Customer Focus in Customer Loyalty.